Analisis Daya Dukung Lahan Pertanian Di Kampung Susweni Distrik Manokwari Timur - Yohana Mofu; Linda Ernawati Lindongi; Rudolf Kristian Tukayo; Antonius Suparno (Agrotek, 2019)
This study aimed to determine the carrying capacity of agricultural land in providing food to meet the needs of the population in Susweni Village, East Manokwari District. This study used the method of determining or comparing the carrying capacity of land by comparing the availability and needs of land. The results of the calculation of carrying capacity using the concept of calculation according to the regulation of the Minister of the Environment No. 17 of 2009 showed that the Susweni Village, East Manokwari District had a land carrying capacity status that was in deficit for the population living in Susweni Village, East Manokwari District. The availability of land of 78.47 ha and the need for land is 302,084 ha. Therefore, the need for land in the Susweni village is greater than the availability of land in the Susweni village. The deficit carrying capacity of the land in Susweni Village, East Manokwari District is strongly influenced by the population which continues to increase every year.